Not writing, and giving 'zero-f**ks' about it: queer(y)ing doctoral 'failure'. Issue 4 (4th July 2017) - Burford, James
ABSTRACT: This article proposes that a queer reading of failure might offer opportunities to re-think the affective-political practice of doctoral writing. It examines data from one case in Aotearoa New Zealand to illustrate how a doctoral student negotiates 'failure' in relation to their writing practice and identity. While higher education researchers have tended to interpret failure as something to avoid, or learn from in the pursuit of normative success, queer research offers us new pathways into analysis. In this article, I argue that we can recognize 'writing failures' as possible modes of being and becoming doctoral. Despite being frequently associated with affective practices of guilt, shame, and disappointment, failure might also open onto alternative feelings such as relief, joy, and satisfaction. Ultimately, the article contends that queer concepts might assist higher education researchers to interrogate normative framings of failure, and to glimpse alternative possibilities for understanding 'success'.